Effect of incorporation of finger millet (Eleusine coracana) on proximate composition, sensory and microbiological properties and shelf life of drinking yoghurt over refrigerated storage - Disanth, E.; Anand Kumar, S.; Susruthan, V.; Piratheepan, S. (University of Sabaragamuwa, Sri Lanka, 2022)
Yoghurt has identified as a suitable carrier for integration of dietary fibre sources in foods. Several research studies revealed consumption of fibre enriched yoghurt may prevent or reduce diabetes, hypercholesterolemia, obesity, cancer, colonic diverticulosis and constipation, ulcerative colitis, whereas promote intestinal micro flora and gastrointestinal immunity. In addition, dietary fibres are capable of improving rheological properties and reducing syneresis in yoghurt (Dabija et al., 2018). Cereals, fruits, vegetables and nuts are good sources of dietary fibres which are absorbed by small intestine and fermented by large intestines. Among cereals, Eleusine coracana (Finger millet) is an excellent source of dietary fibres occurring about 15-20%. However, it is an underutilized cereal in tropical regions, but having an immense potential in the food market due to its nutritional and medicinal values (Göksel Saraç & Dogan, 2016). Further, previous studies demonstrated prebiotic fortification of adding dietary fibres in yoghurt, butter and buttermilk. It is notable that such fermented dairy products were only produced with traditional starter cultures. Thus, it is necessary to produce fibre-enriched yoghurt inoculated with probiotic cultures because it improves gut microbial flora and gastro intestinal immunity. It has been evident by many clinical studies that Lactobacillus acidophilus and Bifidobacterium animalis subsp. lactis BB-12® exhibited beneficial health effects in terms of improved gastrointestinal health and immune functions. Therefore, the aim of the study was to evaluate the effect of addition of finger millet powder on physiochemical properties and microbiological quality of drinking yoghurt.